2007
DOI: 10.1080/09540120701244943
|View full text |Cite
|
Sign up to set email alerts
|

Hunger, waiting time and transport costs: Time to confront challenges to ART adherence in Africa

Abstract: HAL is a multidisciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
417
3
5

Year Published

2008
2008
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 439 publications
(456 citation statements)
references
References 19 publications
31
417
3
5
Order By: Relevance
“…Patients cannot aff ord to travel far, especially when such travel expends 1 or more working days every month. 59 Long waiting times and frequent stock-outs do not support adherence. Public health systems need holistic patientcentred care with appointment systems, evening opening hours, and task-shifting and down-referral of chronic treatment to rural facilities close to home.…”
Section: Integrate Pharmaceutical Management Of Ncds With Existing Inmentioning
confidence: 99%
“…Patients cannot aff ord to travel far, especially when such travel expends 1 or more working days every month. 59 Long waiting times and frequent stock-outs do not support adherence. Public health systems need holistic patientcentred care with appointment systems, evening opening hours, and task-shifting and down-referral of chronic treatment to rural facilities close to home.…”
Section: Integrate Pharmaceutical Management Of Ncds With Existing Inmentioning
confidence: 99%
“…However, most health facilities did not provide nutritional support to their patients on ART. Lack of food has been identified before in some studies as a factor responsible for patients defaulting from their treatments (Hardon et al, 2007;Nachega et al, 2006).…”
Section: Nutritional Supportmentioning
confidence: 99%
“…However, among the 37 qualitative studies included in the review, only two were from developing countries, thus the authors concluded that 'Research is urgently needed to determine patient-important factors for adherence in developing world settings. ' Several reports have been published since then from qualitative studies exploring factors that may affect adherence to ART (Hardon, Akurut, Comoro, Ekezie, Irunde & Gerrits et al, 2007;Kumarasamy, Safren, Raminani, Pickard, James, Krishnan et al, 2005;Malta, Petersen, Clair, Freitas & Bastos, 2005;Nachega, Knowlton, Deluca, Schoeman, Waltkinson, Efron et al, 2006). In an open cohort study of more than 16 000 adult patients that were started on ART in urban Zambia (Lusaka), poor adherence was among the factors found to be strongly correlated with mortality (Stringer, Zulu, Levy, Stinger, Mwango, Chi et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These strategies have mainly been evaluated in high-income countries. Most adherence studies in Africa have focused on home-based support, building self-efficacy and assessing ART costs and adherence (Diabate, Alary, & Koffi, 2007;Hardon et al, 2007;Mukherjee, Ivers, Leandre, Farmer, & Behforouz, 2006;Ramadhani et al, 2007;Simoni et al, 2008;Weidle et al, 2006).…”
Section: Introductionmentioning
confidence: 99%